(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Attualità del diritto di libertà religiosa - 2. La libertà religiosa e la sfida del pluralismo confessionale - 3. L’affermazione del diritto di libertà religiosa in Europa - 4. Evoluzione espansiva del diritto di libertà religiosa. Tradizione anglosassone e approccio europeo ai diritti - 5. Dimensione negativa o di garanzia e dimensione positiva o promozionale del diritto di libertà religiosa - 6. Dimensione positiva dei diritti e obblighi di solidarietà: la logica del sistema pattizio - 7. Il sistema italiano di tutela del diritto di libertà religiosa - 8. Legislazione ecclesiastica e proposte di riforma - 9. Il progetto di legge generale sulla libertà religiosa - 10. Evoluzione del quadro normativo e progetti di riforma - 11. Organizzazioni agnostiche e strutture confessionali: un’assimilazione controversa - 12. Il sistema pattizio come garanzia di pluralismo confessionale e di piena integrazione. Religious freedom and proposals of reform of the Italian law concerning religious denominations ABSTRACT: This paper, after briefly recalling the importance of religious freedom in Western civilization and its progressive identification as a fundamental right all over the world, examines the legal framework of religious freedom in the Italian law system. In doing so, it underlines the distinction between the negative and positive aspects of the right, calling for a different attitude on behalf of the State according to the different common law and civil law systems. In the end, taking into account the principles of the Constitution and the Italian Constitutional Court’s case law, it critically addresses the current debate on the proposal of a State statute concerning the exercise of the right of religious freedom for individuals and, above all, for denominational groups without an agreement with the State.